Penyuluhan Dampak Negatif Penyalanggunaan Narkotika Terhadap Kesehatan di Aceh Tamiang - Cut Khairunnisa; Sidrah Nadira, Cut (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2023)
There are at least three factors that influence students to consume narcotics, namely the family environment, school environment and community environment. Narcotics abuse among students is a serious problem because they are a productive age group and are the next generation to follow. Therefore, health counseling activities for students on drug abuse are needed on an ongoing basis. Responding to this problem, a lecturer at the Faculty of Medicine, Universitas Malikussaleh, has held legal counseling about drug abuse at Aceh Tamiang. This activity is a form of Higher Education Tridarma in which every member of the academic community performs community service to provide solutions to any problems being experienced by the community.